Welfare of horses during killing for purposes other than slaughter - EFSA AHAW Panel (EFSA Panel on Animal Health and Welfare); Søren Saxmose Nielsen; Julio Alvarez; Anette Boklund; Sabine Dippel; Fernanda Dorea; Jordi Figuerola; Mette Herskin; Miguel Angel Miranda Chueca; Eleonora Nannoni; Romolo Nonno; Anja Riber; et al. (EFSA Journal)
Abstract Horses of different ages may have to be killed on‐farm for purposes other than slaughter (where slaughter is defined as killing for human consumption) either individually (i.e. on‐farm killing of unproductive, injured or terminally ill animals) or on a large‐scale (i.e. depopulation for disease control purposes and other situations, such as environmental contamination, disaster management, etc.). The purpose of this opinion is to assess the hazards and welfare consequences associated with the on‐farm killing of horses. The killing procedure is divided into Phase 1 (pre‐killing), which includes the processes (i) handling and moving the animals to the killing place and (ii) restraint of the animals before application of the killing method; and Phase 2 (stunning and/or killing), which includes stunning and killing of the animals (for methods that require one step for stunning and another for subsequent killing) or killing only (for methods that simultaneously stun and kill the animals). Three stunning and/or killing methods for Phase 2 for horses were identified: (i) penetrative captive bolt followed by killing, (ii) firearms with free projectiles and (iii) lethal injection. Welfare consequences that horses may experience during each process (e.g. handling stress, restriction of movement and injuries during restraint) were identified and potential hazards are listed for all phases, along with preventive and corrective measures. Animal‐based measures (ABMs) to assess all identified welfare consequences were proposed. During the application of the stunning and/or killing methods, horses will experience pain and fear if they are ineffectively stunned/killed or if they recover consciousness. A flowchart including ABMs for the assessment of consciousness and death to monitor stunning and killing effectiveness is provided. Additionally, specific practices deemed unacceptable on welfare grounds are listed.